Comparisons of self-reported and register data on sickness absence among public employees in Sweden. Issue 1 (17th August 2007) - Voss, M; Stark, S; Alfredsson, L; Vingård, E; Josephson, M
Abstract : Aim: Self-reported assessments of sickness absence are often performed in epidemiological studies. The objective of this study was to compare the number of sick-leave days according to self-reported data over 12 months with data from the employer's register for the same period. An additional aim was to ascertain whether the self-reported information and the recorded data would show equivalent associations with self-reported general health. Methods: The study was based on a cohort of 4869 municipal employees in Sweden, about 80% women, who answered a questionnaire in 2001–2. The responses provided by the employees included information on number of sick-leave days and self-rated health. Data on sick-leave days, occupation and age were derived from the employers' computerised registers. The questionnaire information on sick-leave days was compared with the corresponding information retrieved from the employer register by means of calculating sensitivity and specificity, using the employers' data as the "gold standard". Results: The annual number of sick-leave days was lower according to the self-reported information than to the register data. For women the agreement between the two sickness absence measures for no sick-leave days, 1–7 days and ≥28 days were 74%, 72% and 67%, respectively. The sensitivity of questionnaire versus register information regarding any self-reported sick-leave day was 91% and the specificity was 74%. Sensitivity and specificity for sickness absence ⩾28 days were 67% and 98%, respectively. The results for men were similar to those for women. Self-reported and recorded sickness absence were both associated with self-rated health. The odds ratios were 7.27 and 8.25, for subjects with ≥28 recorded and self-reported number of sick-leave days respectively, compared to subjects with no sickness absence. Conclusions: Good agreement was found between self-reported and register information on sickness absence. Self-reported data on sickness absence may be useful in common epidemiological applications.